Metodologias ativas para o ensino de estrutura proteica e enzimologia no ensino superior - Oliveira, Cláudia Sirlene de (2022)
Biochemistry is a discipline with enormous potential for contextualization and interdisciplinarity, however, it is seen as one of the most difficult disciplines and with high failure rates among students. Therefore, it is important to adapt teaching strategies to make Biochemistry classes more interesting, to assist the student in the construction of knowledge. This dissertation is divided into two independent studies. In the first study, investigative practical classes were carried out with students from the Biological Sciences undergraduate course at the Federal University of Santa Maria. Students simulated the synthesis of the hormone glucagon, from transcription to construction of the 3D model. The students were motivated, stating that the construction of the protein model contributed to the construction of knowledge about protein chemistry. In the second study, classes were held with students from undergraduate courses in Biological Sciences and Veterinary Medicine at the same university, on the mechanisms of enzyme inhibition. The enzyme acetylcholinesterase from the head of cockroaches of the species Nauphoeta cinerea was used. Students tested different factors that alter enzyme activity in vitro and in vivo. Most of the students showed enthusiasm in working with animals in practical classes, as well as an improvement in their knowledge of enzymology. Thus, in this dissertation, it was possible to demonstrate that the use of investigative practical classes is important for students to build solid knowledge about the contents of the Biochemistry discipline.